2010
DOI: 10.2202/1556-3758.1824
|View full text |Cite
|
Sign up to set email alerts
|

Development and Characterization of Extruded Product Using Carrot Pomace and Rice Flour

Abstract: Dehydrated carrot pomace was added in different proportions (10-30%) to rice flour. The formulation was extruded at different moisture content (17-21%), screw speed (270-310 rpm) and die temperature (110-130°C). The experimental combinations were decided based on central composite rotatable design for four variables at five levels of each variable. The lateral expansion, bulk density, water absorption index, water solubility index, hardness and sensory characteristics were measured as responses. Significant re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
65
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(90 citation statements)
references
References 0 publications
22
65
0
3
Order By: Relevance
“…At higher temperature, starch granule is disrupted and more water is bound to the starch molecule resulting in increased WAI. Kumar et al (2010) examined the increased effect of WAI with increased temperature which is in support of our current findings. WAI has been reported to increase with increase in moisture content of feed (Ding et al .…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…At higher temperature, starch granule is disrupted and more water is bound to the starch molecule resulting in increased WAI. Kumar et al (2010) examined the increased effect of WAI with increased temperature which is in support of our current findings. WAI has been reported to increase with increase in moisture content of feed (Ding et al .…”
Section: Resultssupporting
confidence: 86%
“…Since, in our blend, the proportion of protein is high, the increase might be due to partial protein denaturation at higher temperature (Oikonomou and Krokida 2011). Kumar et al (2010) indicated that WSI increases with increase in fibrous content in the feed formulation, which supports our findings (Fig. 2b).…”
Section: Water Solubility Index (Wsi)supporting
confidence: 88%
See 1 more Smart Citation
“…Briefly, 200 µl of the extracts were mixed with 12.5 µl of Folin-Ciocalteu reagent and then 37.5 µl 20% Na 2 CO 3 in a 96-well legumes, fruits, and vegetables [23]. Studies on the incorporation of pomace into extruded products showed that increased pomace levels beyond a certain level had negative effect on the expansion quality [16,17,20,27,28]. However, recent studies indicated that carrot and cherry pomace incorporation into cornstarch extrudates resulted in better expansion and nutritional quality [18,19].…”
Section: Product Responsementioning
confidence: 99%
“…Lower values of WSI are often associated with the less dextrinization of starch during extrusion. Addition of GP provides insoluble fiber and other hydrophilic groups that can interact with starch to reduce the overall gelatinization, and hold water instead of being solubilized [27,43]. In fact cherry pomace in swelled starch granules trapes water and lowers WSI [18].…”
Section: Water Absorption Index (Wai) and Water Solubility Index (Wsi)mentioning
confidence: 99%